REASONS AND FACTORS ASSOCIATED WITH NOT PERFORMING THE PAP SMEAR TEST: motivos e fatores associados à não realização do exame PAPANICOLAU DO EXAME PAPANICOLAU - de Souza, Lucia Oliveira; Flório, Flavia Florio; Zanin, Luciane (Revista de Ciências da Saúde Nova Esperança, 2026)
The objective of this study was to evaluate the reasons and factors that interfere with non-adherence to the pap smear. Cross-sectional, observational, quantitative study, carried out with 379 women who missed the exam scheduled in 2019 at the ubs of Anori-AM. The volunteers answered a questionnaire containing questions related to uterine cancer and the pap smear, sociodemographic profile and reasons for not adhering to the exam. The relationship between failure to undergo previous exams (dependent variable) and sociodemographic and pap smear-related variables was analyzed. The mean age was 39.5 ± 9.8 years and 25.3% reported not having undergone previous exams. The reasons for non-adherence were lack of interest, fear and shame (82.3%). A significant association was observed with being over 37 years old (or=1.73; 95% ci: 1.02-2.94), not having knowledge about how regularly to take the exam (or=6.09; 95% ci). %: 1.77-20.98) and those who do not know the previous exam recommendations (or=10.45; 95%ci: 5.47-19.96), p<0.05. It is concluded that the reasons for non-adherence are related to personal aspects including lack of interest, fear, embarrassment, and insecurity and, not carrying out previous exams was associated with older women, a lack of knowledge about the regularity and recommendations prior to the exam.